An N-heterocyclic carbene iridium catalyst with metal-centered chirality for enantioselective transfer hydrogenation of imines. Issue 57 (5th July 2017) - Li, Yanjun; Lei, Meng; Yuan, Wei; Meggers, Eric; Gong, Lei
Abstract : A cyclometalating N-heterocyclic carbene iridium complex featuring metal-centered chirality has been developed for the highly enantioselective transfer hydrogenation of imines. Abstract : A cyclometalating N-heterocyclic carbene iridium complex featuring metal-centered chirality was designed and used for the asymmetric transfer hydrogenation (ATH) of imines. Four strongly σ-donating carbon-based substituents (2 carbenes and 2 phenyl moieties), a chirality transfer directly from the stereogenic metal center to the CN bond of substrates, as well as a restriction of catalyst deactivation by steric demanding substituents, render the new complex one of the most efficient catalysts for ATH of cyclic N -sulfonylimines (down to 0.01 mol% cat., 24 examples, 94–98% ee).